Strategi Peningkatan Kinerja Operator Desa dalam Penyaluran Bantuan Sosial di Wilayah Kecamatan Kalinyamatan Kabupaten Jepara - Tatik Marwati; Mamik Indaryani; Joko Utomo (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to describe the strategy for improving the performance of village operators in distributing social assistance in the Kalinyamatan District, Jepara Regency. This research method uses Qualitative Methodology with a descriptive approach by conducting interviews with 12 informants including village heads, village operators and beneficiary families. The results of this study state that the main duties and functions of village operators in the Kalinyamatan District, Jepara Regency in distributing social assistance are focused on data management to ensure it is on target. The process of inputting social assistance data to KPM in the Kalinyamatan District, Jepara Regency is carried out in stages through the integrated SIKS-NG system managed by the Ministry of Social Affairs. The results of the identification of internal and external factors of village operators in distributing social assistance in the Kalinyamatan District, Jepara Regency using SWOT analysis can optimize efficiency, data validity, and accuracy of social assistance targets. The strategy for improving the performance of village operators in the Kalinyamatan District, Jepara Regency is focused on strengthening technical capacity, updating data, and increasing transparency.